Предмет: Математика,
автор: Существо338
(d-6)-(7d+1)=-(4-3d)
Ответы
Автор ответа:
0
(d-6)-(7d+1)=-(4-3d)
d - 6 - 7d - 1 = - 4 + 3d
- 6d - 7 = - 4 + 3d
- 7 + 4 = 3d + 6d
- 3 = 9d
d = 3 : (-9)
d ≈ 0,3
d - 6 - 7d - 1 = - 4 + 3d
- 6d - 7 = - 4 + 3d
- 7 + 4 = 3d + 6d
- 3 = 9d
d = 3 : (-9)
d ≈ 0,3
Автор ответа:
0
внимательно проверьте правильно ли переписан пример?
Похожие вопросы
Предмет: Русский язык,
автор: aa752271055
Предмет: Математика,
автор: bfukgdujh
Предмет: Английский язык,
автор: anarorucov2009
Предмет: Литература,
автор: Aleksandrina503